Molecular Characterisation of Aeromonas Species Isolated from Water and Selected Food Molecular Characterisation of Aeromonas Species Isolated from Water and Selected Food - Rajab, Mohd Kamil (1999)
Three species of Aeromonas; A. hydrophila (60 isolates), A. sobria (34 isolates) and A. caviae(113isolates) were isolated from beef, milk, freshwater prawns, fish, and water from fishpond. A. hydrophila was predominant in fish and freshwater prawn, whereas A. caviae was predominant in the milk and water samples. A. sobria was only found in freshwater prawn, water and fish samples. The results of the study indicated that all the five different sources examined were potential vector for Aeromonas in Malaysia. The percentage of antibiotic resistant among Aeromonas species was varying according to its origin. A. hydrophila was more resistant towards ampicillin, bacitracin, carbenicillin and erythromycin. Most of the A. sobria isolates were resistant to ampicillin, bacitracin, carbenicillin and streptomycin and A. caviae was resistant to ampicillin, bacitracin and carbenicillin. The multiple antibiotic resistance (MAR) index of A. hydrophila, A. sobria and A. caviae ranged between 0.08 to 0.66, 0.16 to 0.66, and 0 (zero) to 0.5, respectively. Hence, the MAR indexing of the Aeromonas strains showed that more than 90% originated from high were detected in 50 of the 60 A. hydrophila isolates and 35 plasmid profiles were identified. The plasmid size ranged from 1.4 to 7.0 MDa. Plasmids of 1.4 to 4.1 MDa were detected in 28 of the 34 A. sobria isolates tested, while six isolates were found to be plasmidless. Their plasmid patterns were grouped into 18 patterns. Twenty-one plasmid patterns were found from A. caviae with plasmid sizes ranging from 1.4 to 8.0 MDa. In general, Aeromonas species under study harboured high number of plasmids. The plasmid analysis indicated the presence of more than one clone with the same antibiotic resistance patterns. The data obtained indicated that the samples sources tested form a reservoir for multiple-resistant and plasmid containing Aeromonas species in the study area. The RAPO-PCR was performed to characterise the Aeromonas spp. by using three random primers (GEN26003, GEN26007, and GEN26010). Among the Aeromonas spp., A. hydrophila was found to be differentiated by the three primers distinctively. Primer GEN26003 was the most suitable primer to differentiate the isolates. The three primers generated polymorph isms in all 207 strains of Aeromonas species tested, producing bands ranging from 0.24 to 4.5 Kb. The RAPO profiles revealed a wide variability and no correlation with the source of isolation. In addition, the RAPO data suggested that the Aeromonas strains might have originated from diverse sources.